(untitled) (Texas Journal of Medical Science, 2023)
The autoprotective activity of Glyzimed, which contains herbal plants Hypericum perforatum L., Ziziphora pedicellata Pazij et Vved., Mediazia macrophylla and rhizome parts of Glycyrrhiza glabra L. was studied on experimental animals. Experimental studies were carried out on male white mice weighting 18-22 g. The comparative actoprotective activity of glyzimed, piracetam, and phytin, was studied on adult white mice, which were exposed to the forced swimming until the development of obvious signs of fatigue and the grip strength of paws was tested using a grip strength system device (Ugo Basile Srl, Italy). The animals of the experimental groups were intragastrically administered an aqueous solution of glyzimed using a syringe with a metal probe at doses of 10, 25 and 50 mg/kg, piracetam - 100 mg/kg and phytin - 200 mg/kg one day and one hour before the start of the experiment. Antihypoxants statistically significantly increase the maintaining of physical performance, and activity of glyzimed is almost twice superior to piracetam. Glyzimed can be proposed as an effective actoprotective medicine.